Religious Violence and National Security in Nigeria, 1999 – 2011 - Afolabi, Oluwaseun Olawale (2016)
Nigeria which is multi-ethnic and multi-religious in nature is faced with religious violence. Religion that supposed to be a unifying factor among several ethnic groups in Nigeria has turned out to be one of the catalysts that are causing destruction of lives and properties due to narrow-mindedness, misunderstanding, fundamentalism and fanaticism of religious adherents. Several political problems take on religious dimensions; manipulated by politics, poverty, illiteracy and ignorance in Nigeria. Violence based on religious affiliation and religious policies have indeed caused physical and psychological damage to several people thereby legitimising religious schism among Nigerians who simply have different religious affiliations. This upheaval threatens the national security of the country. Thus, study will make use of survey methodology in examining the effect of religious violence in Nigeria from 1999 to 2011 and intends to find out how religion which has been the bone of contention can bring peaceful co-existence. Keywords: Religion; Violence; National Security; Christianity; Muslim